P3-S2.04 Clinical evaluation of the BD HSV2 Qx assay for the direct qualitative testing of HSV2 as compared to viral culture and a laboratory-based PCR assay using male and female external anogenital lesions. (10th July 2011) - Hires, L; Van Der Pol, B; Williams, J; Corey, L; Hook, E W; Nye, M; Taylor, S; Martens, M; Mena, L; Warren, T
Abstract : Background: To compare the performance characteristics of the BD ProbeTecTM HSV2 Qx Assay* on the BD ViperTM System in Extracted Mode to viral culture and a well-characterised molecular assay for the detection of HSV2. External anogenital lesions were sampled with two different collection devices: a universal viral transport (UVT) kit and a BD Qx swab (QS) kit*. Methods: Eleven geographically diverse clinical centers participated in the study, with nine of the sites enrolling participants. The UVT was collected first followed by the QS specimen. A portion of each UVT specimen was transferred to a Qx Diluent Tube (diluted UVT) and a cryovial. The remainder of the UVT in the original tube was frozen at −70°C and sent to one of two sites for HSV viral culture using the ELVIS®HSV ID and D3 Typing Test System (Diagnostic Hybrids, Inc). The diluted UVT and QS specimens were shipped to one of three sites for HSV testing on the BD Viper. The UVT aliquot in the cryovial was stored at −70°C and shipped to the University of Washington for PCR testing for HSV. Results: Subjects (n=508) were enrolled between February and August of 2010 with 501 UVT and 498 QS samples available for comparison to ELVIS culture, and 506 and 503 samples, respectively, for comparison to the PCR assay. The sensitivity and specificity of the BD HSV2 Qx Assay were compared to ELVIS culture and the positive (PPA) and negative (NPA) per cent agreement of the assay was compared to the HSV PCR assays for both specimen types. Of the BD HSV2 Qx Assay positive, culture negative samples, 46/51 (90.2%) of the UVT and 49/60 (81.7%) of the QS were positive by HSV2 PCR see Abstract P3-S2.04 table 1 . Conclusions: The BD HSV2 Qx Assay on the BD Viper had excellent agreement with the lab developed PCR assay for diagnosis of HSV2, which is currently recognised as one of the best available tests for the detection of HSV. A commercially available molecular-based assay for the detection of HSV would not only improve detection and reduce turn-around time on results, but may also obviate the need for stringent transport conditions required for HSV culture. *Product not for sale, for investigational use only in the USA.